INVESTIGATION OF LOCALIZED RAPID SOOT OXIDATION USING METALASSISTE HIGH FREQUENCY ELECTROMAGNETIC HEATING - AZIZ AL-WAKEEL, HAITHAM BEHNAM (2015)
Soot is a black carbon, produced from the incomplete combustion of diesel fuel, seen as a black smoke when it is emitted from diesel engines. Soot has dangerous impacts on the environment and human health. Hence, there are many regulations to reduce soot emissions. Current measures include the use of particulate matter filters to trap the soot from the exhaust gas. However, the increasing trapped soot in the filter leads to blockage of the filter, resulting in reducing of the engine efficiency and may lead to the engine damage. Therefore, filter regeneration strategies are used to oxidize the soot. One of the efficient strategies is high frequency electromagnetic or microwave heating. The drawbacks of microwave heating for soot filter regeneration are nonuniform regeneration, non-effective on soot of a small thickness, and excessive heating in the presence of a thick soot layer, which damages the filter.